Substrate-dependent activation of LONP1 informs on proteolytic regulation and ATPase motor function - Jeffrey T. Mindrebo; Gabriel C. Lander (Proceedings of the National Academy of Sciences, 2025)
AAA+ enzymes use energy from ATP hydrolysis to remodel diverse cellular targets. Structures of substrate-bound AAA+ complexes suggest that these enzymes employ a conserved hand-over-hand mechanism to thread substrates through their central pore. However, the fundamental aspects of the mechanisms governing motor function and substrate processing within specific AAA+ families remain unresolved. We used cryoelectron microscopy to structurally interrogate reaction intermediates from in vitro biochemical assays to inform the underlying regulatory mechanisms of the human mitochondrial AAA+ protease, LONP1. Our results demonstrate that substrate binding, rather than nucleotide binding, activates the assembly and allosterically regulates proteolytic activity. The N-terminal domain plays a critical role in this process and facilitates the initial stages of substrate selection and engagement. Moreover, structures of LONP1 actively degrading a substrate in the presence of ATP provide important context to the conventional understanding of the hand-over-hand translocation mechanism, suggesting that ATP hydrolysis is likely not limited to a single position in the right-handed spiral during the hand-over-hand translocation mechanism.